2014
DOI: 10.5901/mjss.2014.v5n23p1405
|View full text |Cite
|
Sign up to set email alerts
|

Competencies Required for the Facilitation of Online Learning Courses: An Online Teaching Assistants Competency Based Approach

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 21 publications
1
3
0
9
Order By: Relevance
“…Lecturers who participated in the study might have identified these instructional opportunities provided by online facilitation to engage and interact with students at a distance. This finding is in line with Motladi, (2014) who found that teaching assistants were ready to participate in online facilitation as they already acquired basic computer skills that would promote actively interaction with the students.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Lecturers who participated in the study might have identified these instructional opportunities provided by online facilitation to engage and interact with students at a distance. This finding is in line with Motladi, (2014) who found that teaching assistants were ready to participate in online facilitation as they already acquired basic computer skills that would promote actively interaction with the students.…”
Section: Discussionsupporting
confidence: 87%
“…It has been established that online facilitation strengthens the relationship among the learners and between learners and their tutors. Online facilitation is an ODL instructional delivery medium that requires competent personnel with appropriate skills and suitable attitude to moderate teaching-learning process in virtual learning environments (Motladi, 2014). An online facilitator is an expert saddled with the responsibilities to galvanise available learning resources to stimulate interaction with the learners and support their learning process, as they take part in online instruction (Goga, 2010).…”
Section: Bridging the Instructional Gaps In Odl Through Effective Online Facilitationmentioning
confidence: 99%
“…Son las competencias las que hacen que el sujeto afronte y regule adecuadamente un conjunto de tareas y funciones predeterminadas (Dias, 2010). El tutor en educación a distancia, tiene una diversidad de roles que se distinguen de los que se aplican en el aula en la modalidad presencial, por lo tanto, se necesitan diferentes competencias para realizar su trabajo de manera satisfactoria (Kopp et al, 2012;Setlhako, 2014). Dados los trabajos seleccionados, se discuten varias competencias considerando el papel del tutor en la educación a distancia.…”
Section: Resultados Y Discusionesunclassified
“…De esta manera, la noción de competencia se ha utilizado comúnmente para referirse a la capacidad necesaria para realizar una determinada actividad, o sea, al saber cómo hacer, para poner en práctica los conocimientos adquiridos (Setlhako, 2014;Tenório et al, 2016;Skorková, 2016). Para Fleury y Fleury (2001, p. 188), competencia es "saber cómo actuar de manera responsable y reconocida, lo que implica movilizar, integrar, transferir conocimientos, recursos y habilidades, que agregan valor económico a la organización y valor social al individuo", denotando, de esta manera, su contribución personal y para la efectividad de las acciones en el centro de las actividades profesionales.…”
Section: Enfoque De Competenciaunclassified
“…Scholars have argued that online facilitation strengthens relationships among the tutors, distance learners and learning resources (Adesina, 2020). It remains an ODL instructional delivery approach that requires competent personnel with appropriate skills and favourable attitude to moderate teaching-learning process in virtual learning environments (Motladi, 2014). This intervention is considered as an emerging instructional delivery medium, which engenders active interaction among critical instructional elements in ODL.…”
Section: Leveraging the Capabilities Of Online Facilitation To Bridgementioning
confidence: 99%